Analyzing the Performance of Upper Elementary and High School Students in Activities Involving Fractions and Associated Ideas Analisando o Rendimento de Alunos das Séries Finais do Ensino Fundamental e do Ensino Médio em Atividades Envolvendo Frações e Idéias Associadas - Adegundes Maciel; Marcelo Câmara dos Santos (Universidade Estadual Paulista, 2008)
This article presents partial results of a broader study. Here we try to identify how to show the performance of students in problem-solving activities including the ideas associated with fractions, as a function of their level of education. Six hundred and thirty students participated in this research, with an average of ninety per grade, all from the public school system in Pernambuco. The instrument consisted of 10 items including three ideas associated with fractions (part-whole, quotient and operator), varying the type of quantity involved (discretes and continuous). The results show differences in behavior of fifth and sixth grade students when they are asked to vary the type of quantity and the idea of fraction involved in an item. It also was possible to observe that the types of errors made by students present a certain stability with the development of education. Keywords: Mathematics Education. Fraction. Idea of Fraction. Equivalence. Este trabalho apresenta parte dos resultados de um estudo mais amplo3. Aqui buscamos identificar como se comporta o rendimento de alunos em atividades de resolução de problemas envolvendo as idéias associadas às frações, em função de sua escolaridade. Participaram da pesquisa 630 alunos de escolas públicas de Pernambuco, com uma média de 90 alunos por série. O instrumento constou de 10 itens envolvendo três idéias associadas às frações (parte-todo, quociente e operador), variando o tipo de quantidade envolvida (discreta e contínua). Os resultados mostram um comportamento diferenciado dos alunos do terceiro Ciclo (quinta e sexta séries) quando se faz variar o tipo de quantidade e a idéia de fração envolvida no item. Foi possível identificar também que os tipos de erros cometidos pelos alunos apresentam certa estabilidade com o desenvolvimento da escolaridade. Palavras-chave: Educação Matemática. Fração. Idéia de Fração. Equivalência.